MICROBIAL COMMUNITY ASSOCIATED WITH AMBROSIA BEETLE, Euplatypus parallelus ON SONOKEMBANG, Pterocarpus indicus IN MALANG - Hagus Tarno; Erfan Dani Septia; Luqman Qurata Aini (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2016)
Recently, most of sonokembang, Pterocarpus indicus trees are dying in Malang. In 2012, the death rate of trees reached ca. 11%. In addition, death of trees spread to other regencies in East Java. Euplatypus parallelus is a specific species of ambrosia beetles that were the causal agents to the dying and wilting of sonokembang trees in Malang. Wilting is caused mainly by the pathogenic fungi carried by ambrosia beetles. To confirm the microbial communities related to E. parallelus that attack sonokembang, E. parallelus and some attacked trees were collected in Malang city. Isolation and identification of these species were conducted at the Laboratory of Mycology, Faculty of Agriculture, University of Brawijaya and Laboratory of Molecular Biology, Islamic State University, Malang. Results showed that there were nine microbes including five genera of fungi, two genera of yeasts and one genus of bacterium were identified. The microbial communities that were found namely Aspergillus spp., Penicillium spp., Trichoderma spp., Fusarium spp., Acremonium spp., Gliocladium spp. (fungi), Streptomyces spp. (bacteria), Saccharomyces spp., and Candida spp. (yeast).